On Semisecond Submodules - Zainab Saadi; Ghaleb Ahmed (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2020)
Let  be a right module over a ring  with identity. The semisecond submodules are studied in this paper. A nonzero submodule  of   is called semisecond if    for each . More information and characterizations about this concept is provided in our work.